Effectiveness of Antimicrobial Photodynamic Therapy in the Treatment of Periodontitis: A Systematic Review and Meta-Analysis of In Vivo Human Randomized Controlled Clinical Trials - Snehal Dalvi; Stefano Benedicenti; Tudor Sălăgean; Ioana Roxana Bordea; Reem Hanna (MDPI AG, 2021)
This systematic review and meta-analysis evaluated antimicrobial photodynamic therapy (aPDT) efficacy in periodontitis. The review protocol was conducted in accordance with PRISMA statements, Cochrane Collaboration recommendations and is registered in PROSPERO (CRD 42020161516). Electronic and hand search strategies were undertaken to gather data on in vivo human RCTs followed by qualitative analysis. Differences in probing pocket depth (PPD) and clinical attachment level (CAL) were calculated with 95% confidence intervals and pooled in random effects model at three and six months. Heterogeneity was analyzed, using Q and I2 tests. Publication bias was assessed by visual examination of the funnel plot symmetry. Sixty percent of 31 eligible studies showed a high risk of bias. Meta-analysis on 18 studies showed no additional benefit in split mouth studies in terms of PPD reduction (SMD 0.166; 95% CI −0.278 to 0.611; P = 0.463) and CAL gain (SMD 0.092; 95% CI −0.013 to 0.198; P = 0.088). Similar findings noted for parallel group studies; PPD reduction (SMD 0.076; 95% CI −0.420 to 0.573; P = 0.763) and CAL gain (SMD 0.056; 95% CI −0.408 to 0.552; P = 0.745). Sensitivity analysis minimized heterogeneity for both outcome variables; however, intergroup differences were not statistically significant. Future research should aim for well-designed RCTs in order to determine the effectiveness of aPDT.